Development of an Earth Nullschool-Assisted Learning E-Module on Climate Change Topic - Puan Cahyani Gusmer; Tugiyo Aminoto; Erlida Amnie (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2026)
Climate change is a global issue requiring a strong scientific understanding, particularly of atmospheric dynamics and the factors driving rising global temperatures. However, physics learning on this topic remains dominated by theoretical approaches, limiting students’ opportunities to analyze real-time data. This study aims to develop an Earth Nullschool-assisted learning e-module on climate change materials as an interactive, contextual digital learning medium that supports 21st-century skill enhancement. This research employed a research and development (R&D) method using the 4D development model, comprising define, design, develop, and disseminate stages. The study was limited to the development stage, as the main objective was to produce a valid and feasible model. The research subjects were grade X students of SMAN 10 Kota Jambi, selected using random sampling. The instruments included validation questionnaires from material, media, and pedagogical experts, as well as student response questionnaires. Quantitative data were analyzed using a Likert scale, while qualitative analysis was obtained from comments, critiques, and suggestions from validators and teachers. The results show that the e-module received a “very feasible” rating from the three experts and a positive response from the teacher and students. Thus, the Earth Nullschool- assisted e-module meets feasibility criteria as learning medium for climate change topic.